2020
DOI: 10.1183/13993003.01272-2020
|View full text |Cite
|
Sign up to set email alerts
|

European Respiratory Society statement on sleep apnoea, sleepiness and driving risk

Abstract: Obstructive sleep apnoea (OSA) is highly prevalent and is a recognised risk factor for motor vehicle accidents (MVA). Effective treatment with continuous positive airway pressure (CPAP) has been associated with a normalisation of this increased accident risk. Thus, many jurisdictions have introduced regulations restricting the ability of OSA patients from driving until effectively treated. However, uncertainty prevails regarding the relative importance of OSA severity determined by the apnoea-hypopnoea frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 227 publications
(289 reference statements)
0
39
0
Order By: Relevance
“…Obstructive sleep apnea (OSA) is characterized by complete or partial collapse of the upper airway during sleep, intermittent snoring, increasing inspiratory efforts, sleep fragmentation, and cyclic hypoxemia and hypercapnia ( 1 ). Excessive daytime sleepiness (EDS) is a major symptom of OSA, occurring in approximately a quarter to half of OSA patients ( 1 , 2 ) and is associated with increased risk of accidents at work or while driving ( 3 , 4 ). Continuous positive airway pressure (CPAP) is the most effective and commonly used treatment for OSA ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obstructive sleep apnea (OSA) is characterized by complete or partial collapse of the upper airway during sleep, intermittent snoring, increasing inspiratory efforts, sleep fragmentation, and cyclic hypoxemia and hypercapnia ( 1 ). Excessive daytime sleepiness (EDS) is a major symptom of OSA, occurring in approximately a quarter to half of OSA patients ( 1 , 2 ) and is associated with increased risk of accidents at work or while driving ( 3 , 4 ). Continuous positive airway pressure (CPAP) is the most effective and commonly used treatment for OSA ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…CPAP application through a tightly fitted nasal or oronasal mask, at a sufficient pressure level titrated in each patient, prevents upper airway collapse and the pathophysiological consequences of OSA. CPAP treatment improves EDS either assessed subjectively by the Epworth Sleepiness Scale (ESS) or objectively by the Maintenance of Wakefulness Test (MWT) ( 5 ) and prevents sleepiness-related driving accidents ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Obstructive sleep apnea is highly prevalent, with recent general population studies indicating that 20% to 30% in men and 10% to 15% in women have moderate or severe sleep-disordered breathing. 13,14 Excessive daytime sleepiness (EDS), a major symptom of OSA, is reported in approximately 25% to 50% of OSA patients 15 and studies have shown that EDS while driving is an important factor in road accidents or work-related accidents. 13,16 While OSA has been recognized by the European Respiratory Society (ERS) as a risk factor for road accidents, 13 there is still uncertainty about the relative importance of OSA severity indices of OSA, and the degree of sleepiness as a risk factor for accidents.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical population samples (i.e., patients admitted or followed for disease other than OSAS), on average the BQ showed a higher sensitivity compared to the STOP-Bang. Clearly, the data indicate that questionnaires neither reliably rule in nor rule out OSA (20).…”
Section: Osas and Questionnairesmentioning
confidence: 81%
“…The recently published European Respiratory Society statement on sleep apnoea, sleepiness and driving risk (20) concludes that certainly with regards to driving none of the existing screening questionnaires is satisfactory and calls for more research on new questionnaires. In the general population, extreme variation can be found in the sensitivities and specificities for all established questionnaires (ESS sensitivity 18-85%, specificity 22-98% (21-23); BQ sensitivity 40-97%, specificity 6-100% (24-30); STOP sensitivity 33-98%, specificity 10-95% (31); STOP-Bang sensitivity 0-100%, specificity 0-100% (25,(31)(32)(33), even taking into account the cut-off thresholds for OSA (AHI ≥5 events/h, AHI ≥15 events/h, AHI ≥30 events/h).…”
Section: Osas and Questionnairesmentioning
confidence: 99%